Vegetation Composition and Natural Regeneration in a Tropical Montane Forest Following Anthropogenic Disturbances - Kipkorir , J. N.; Onkware , A. O.; Kimutai , N.; Mulei , J. M. (African Journal of Education,Science and Technology (AJEST), 2025)
The Mau complex in Kenya is a range of highlands covered by natural forests known as South -West Mau, Eastern Mau, Ol‟donyoPurro, Transmara, Maasai Mau, Southern Mau and Western Mau. The Western Mau Forest is located at an altitude between 2,000 and 2,600 m and between latitude 0 0 10‟ 46” S to 00 17‟ 42” S and longitude of 35 0 27‟ 05” E to 350 39‟ 42” E. The Mau complex is an important source of many rivers that flow into Lake Victoria basin, yet it has been under pressure for conversion into farmland. A study was carried out on the vegetation composition, regeneration and anthropogenic disturbances. The study was conducted using 500 m long and 2 m wide belt transects in forest zone, 30 m long, 5 m wide transects both in transition zone and grasslands. The forest zone transects were subdivided into 50 m by 2 m subplots, transition and grassland zone transects were subdivided into 5 m by 5 m subplots. In all subplots, a 1 m by 1 m quadrat was placed at the centre. Data were collected on occurrence of fern, liana, shrub, seedling (< 1 cm), sapling (DBH 1 -9.9 cm) and tree (DBH ≥ 10 cm) species. The data were used to calculate abundance, diversity and regeneration. The data were analyzed using analysis of variance and chi-square statistic. Shannon-Weiner index was used to quantify species diversity. Two hundred and twenty three (223) vascular plant species belonging to eighty three (83) families were identified. The Asteraceae had the highest numb er of species (18) followed by Fabaceae. Forty (40) families had a single species each. There were more plant species in the transition zone than forest and grassland zone. The forest was dominated by seedlings and saplings (DBH ≤ 3 cm); the diameter size distribution was reverse J-shaped, indicating that the forest has a good regeneration potential. Species diversity was significantly higher in the forest (3.5 to 4.5) than transition zone (2.0 to 3.5) or grassland (1.5 to 3.0). There was a significant human disturbance, and this affected the species composition, diversity and forest regeneration.